A Study On Mechanical And Electrical Properties Of Hybridized Graphene-Carbon Nanotube Filled Conductive Ink - Mokhlis, Maizura (2020)
Many researchers are now competing to fabricate an electronic device to meet the technological demand by using new conductive materials. There are several varieties of conductive inks on the market and it is crucial to choose the right ink fitting in the electronic applications. Conductive ink is a special type of ink that allows an electric current to flow through the ink. The conductive ink-filled epoxy is also known as conductive composites because the ink itself is based on more two ingredients such as filler, binder, and hardener. As interconnect material, the conductive inks should feature good electrical, mechanical and thermal properties. Nonetheless, to-date, there are some issues with current conductive ink that available in the market namely printing quality, high electrical resistivity as well as inferior mechanical strength. Therefore, this study aims to produce highly functional conductive ink using two types of carbon-based conductive fillers with epoxy as a binder. More specifically, graphene nanoplatelets (GNP) and multiwalled carbon nanotube (MWCNT) were used to produce the hybrid conductive ink. As a baseline, both fillers, GNP and MWCNT with epoxy were formulated separately using a minimum percentage at the beginning and the amount of filler was increased based on the conductivity level required. The percentage of filler for GNP was varied from 10-35 wt.% while for MWCNT for by 3- 8 wt.%. It is very important to make sure the materials are in contact with each other and therefore the movement of an electron will become easier. Following this, the hybridization of these two materials was made to produce conductive ink with enhanced functionality. The fabrication of the ink was carried out by using a direct mixing method starting from the formulation of the ink, mixing process, printing process and curing process to produce highly conductive hybridized ink. This research also studies the effect of the temperature on electrical, mechanical properties and surface roughness of the hybrid conductive ink using a varying amount of filler for both GNP and MWCNT inks. The electrical properties and the mechanical properties were assessed using a Four-point probe by following the ASTM F390 and a Dynamic Ultra Microhardness using ASTM E2546-15 as a guideline. The experimental results demonstrate an improvement in electrical conductivity. GNP showed higher resistivity around 38 kohm/sq whereas MWCNT showed much lower resistivity around 3.3 kohm/sq. When the hybridization occurs, the result obtained somewhat lower than MWCNT about 2.9 kohm/sq possibly due to the synergistic effect between the GNP and MWCNT, with better distribution and tunneling of electrons between both carbon-based conductive fillers. For mechanical properties, the hardness of hybrid ink is lower hence high in elastic modulus compared to GNP and MWCNT due to local stress concentration in the matrix. Furthermore, the surface roughness of hybrid resulted a smooth surface with the value of 0.833 µm compared to individual fillers. Smooth surface allow continuous conductive line formation without shorting risk.